2020
DOI: 10.3389/fimmu.2019.02999
|View full text |Cite
|
Sign up to set email alerts
|

Opioids Impair Intestinal Epithelial Repair in HIV-Infected Humanized Mice

Abstract: Intestinal barrier dysfunction and subsequent microbial translocation play crucial roles in persistent immune activation leading to HIV disease progression. Opioid use is associated with worse outcome in HIV-infected patients. The exacerbated disease progression by opioids is mainly driven by excessive intestinal inflammation and increased gut permeability. The objective of this study is to investigate how opioids potentiate HIV disease progression by compromising intestinal barrier function and impairing inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 45 publications
2
36
1
Order By: Relevance
“…We also found a decrease in the abundance of Ruminococcaceae bacteria in the model group. Interestingly, some studies have suggested that Ruminococcaceae is negatively correlated with apoptosis of intestinal epithelial cells and IL-6 levels in mice [32], indicating that decreased abundance of Ruminococcaceae may aggravate pelvic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…We also found a decrease in the abundance of Ruminococcaceae bacteria in the model group. Interestingly, some studies have suggested that Ruminococcaceae is negatively correlated with apoptosis of intestinal epithelial cells and IL-6 levels in mice [32], indicating that decreased abundance of Ruminococcaceae may aggravate pelvic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In a 2020 study, it was found that both letrozole and SFZYD exert their therapeutic effect in part through restoration of the gut microbiota; they both attenuated the Firmicutes/Bacteroidetes ratio, which was elevated in the untreated endometriotic group, and restored α-diversity and Ruminococcaceae abundance in the gut microbiota [ 138 ]. Loss of Ruminococcaceae may exacerbate peritoneal inflammation, as it may be negatively correlated to apoptosis of intestinal epithelial cells and murine IL-6 levels [ 139 ]. Therefore, these treatments at least partially function through restoring gut microbiota health.…”
Section: What Can This Mean For Endometriosis Carementioning
confidence: 99%
“…Some bacteria strains from Ruminococcaceae , Lachnospiraceae , and Alloprevotella are known to generate SCFA in the intestine. [ 38,39 ] Therefore, we further studied the effect of spores‐dex on other SCFA‐producing bacteria. As shown in Figure 5d and Figure S10 (Supporting Information), eight genera of SCFA‐producing bacteria were analyzed.…”
Section: Figurementioning
confidence: 99%